2015
DOI: 10.1002/nau.22731
|View full text |Cite
|
Sign up to set email alerts
|

Adjustable versus non‐adjustable male sling for post‐prostatectomy urinary incontinence: A prospective clinical trial comparing patient choice, clinical outcomes and satisfaction rate with a minimum follow up of 24 months

Abstract: Given the choice between the two types of MS, more men chose adjustable Argus over non-adjustable AdVance sling. There was no significant difference in the clinical outcome, social continence and overall patient satisfaction rates between the two types of MS in the short term. Neurourol. Urodynam. 35:482-486, 2016. © 2015 Wiley Periodicals, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
24
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 17 publications
2
24
0
Order By: Relevance
“…The majority of previous studies assess the success of the AdVance sling using improvement in daily pad use and quality of life questionnaires . Recently, two small Australian series have reported on the outcomes of the AdVance sling . Habashy et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of previous studies assess the success of the AdVance sling using improvement in daily pad use and quality of life questionnaires . Recently, two small Australian series have reported on the outcomes of the AdVance sling . Habashy et al .…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Chung et al . reported that 16 of 19 men treated with the AdVance sling achieved social continence (0 or 1 PPD) at a mean follow‐up of 33 months …”
Section: Discussionmentioning
confidence: 99%
“…Chung et al 11 analyzed outcomes as well as patients' decisions of 44 patients who were offered adjustable or fixed male slings due to persistent stress urinary incontinence. Interestingly, a majority of patients (57%) chose the adjustable ARGUS classic male sling, most probably because of the appealing opportunity to increase continence rates by repeated adjustments as hypothesized by the authors.…”
Section: Discussionmentioning
confidence: 99%
“…The adjustable MS has a theoretical advantage over non-adjustable MS because the sling can be revised easily to provide further urethral compression in the event of persistent and/or recurrent urinary incontinence without the need for another MS or salvage AUS surgery. Chung reported that more men chose adjustable over non-adjustable MS when given the options despite no significant difference observed in the clinical outcomes and similar patient satisfaction rate (14). …”
Section: Methodsmentioning
confidence: 99%